Microencapsulated Pomegranate Peel Extract Induces Mitochondrial Complex Iv Activity and Prevents Mitochondrial Cristae Alteration in Brown Adipose Tissue in Mice Fed on a High-Fat Diet+ - Poblete-Aro, C (Cambridge University Press, 2021)
Pomegranate peel is an agro-industrial residue obtained after fruit processing with high total polyphenol (TP) content, making it an attractive by-product for its reuse. Pomegranate peel extract (PPE) and its bioactive compounds have shown positive effects on obesity models. Effects on favouring mitochondrial biogenesis and function have also been described. However, once phenolic compounds are extracted, their stability can be affected by diverse factors. Microencapsulation could improve PPE stability, allowing its incorporation into functional foods. Nevertheless, studies on the potential biological effects of PPE microparticles (MPPE) in obesity models are lacking. This study aims to evaluate the effect of MPPE on brown adipose tissue (BAT) mitochondrial structure and function and metabolic alterations related to obesity in mice fed a high-fat diet (HFD). PPE was microencapsulated by spray drying using inulin (IN) as a wall material and physically-chemically characterised. Eight-week-old male C57BL/6J mice (n 40) were randomly distributed into five groups: control diet (CD), HFD, HFD + IN, HFD + PPE (50 mg/kg per d TP) and HFD + MPPE (50 mg/kg per d TP), for 14 weeks. A glucose tolerance test and indirect calorimetry were conducted. Blood and adipose tissue samples were obtained. MPPE supplementation prevented HFD-induced body weight gain (P < 0·001), fasting glycaemia (P = 0·007) and total cholesterol rise (P = 0·001). MPPE resulted in higher BAT mitochondrial complex IV activity (P = 0·03) and prevented HFD-induced mitochondrial cristae alteration (P = 0·02). In conclusion, MPPE prevented HFD-induced excessive body weight gain and associated metabolic disturbances, potentially by activating complex IV activity and preserving mitochondrial cristae structure in BAT in mice fed with a HFD. © 2021 Cambridge University Press. All rights reserved.